Intensification oof Livestock production by smallholder and landless farmers in India - Das, K S; Singh, A K; Mondal, S K; Rahman, F H; De, H K; Pal, P P; Roy, S K (Indian Farming, 2017)
From the available facts and figures, it is evident that livestocksector is the backbone of Indian agrarian economy which is mainlydependant on small holders and landless farmers. The wide variety oflivestock species has the capability to produce at their optimum level ifthey are managed properly. Therefore, a holistic approach isrequired at every different levels to meet out the future demand ofanimals products, to solve the challenges and to safeguard the poorlivestock producers.